Covalent adsorption of functional groups on [N]-carbophenes - Junkermeier, Chad E.; Psofogiannakis, George; Paupitz, Ricardo [UNESP] (IOP Publishing, 2022)
Starting from the planar molecule 1,3,5-trihydroxybenzene, Du et al reported synthesizing one of a couple of possible 2D materials: graphenylene or 3-carbophene [1]. 3-carbophene is a member of a novel class of two-dimensional covalent organic framework, [N]-carbophenes (carbophenes). Using a high throughput method, we computed the formation energies and conduction properties of 3-, 4-, 5-, and 6-carbophenes with hydroxyl (OH), carbonyl (CO), nitro (NO2), amine (NH2), carboxyl (COOH) functional groups replacing hydrogen terminating agents. Five hundred and nine structures with randomly picked motifs, with functionalizations from a single functional group per cell to fully functionalized were studied. Our results demonstrate a negatively sloped linear relationship between the degree of functionalization and formation energy when the type of functional group and type of carbophene are held constant. The decrease in formation energy with functionalization makes Du's synthesis of functionalized 3-carbophene more creditable. The type of carbophene, type of functional group, and the degree of functionalization all play a role in the band structure of the materials. For example, CO functional groups may lead to a mid-gap state pinned to the Fermi level, whereas the other functional groups studied keep the semiconducting nature of pristine carbophene. Thus, because carbonyl functional groups are often present in defected carbon systems, care should be taken to limit the amount of oxygen in carbophene devices where the band gap is important. Thus, this work strengthens the hypothesis of Junkermeier et al's hypothesis that Du et al synthesized 3-carbophene and not graphenylene [2].
Keywords: 2D Materials; adsorption; functional groups; graphenylene; N-Carbophenes